Teslibras: o diário de uma experiência de ensino do teatro aos surdos - DAVID, Luciano Santiago (2021)
This monograph will be presented as the final work for the conclusion of the course, Full Degree Theater, from the Federal University of Pará, through the Institute of Art Sciences, with the following title: TESLIBRAS: the diary of an experience teaching theater to the deaf. Its main objective is to create and record methods and adaptations for the teaching of the Theater to deaf people. Counting as a counselor: Profª Esp. Uisis Paula da Silva Gomes and Coorientadora: Profª. Dr. Olinda Margaret Charone, the same is built according to the scientific methodology case study, conducted by way of a field study, with collection of material generated by means of video photos and notes. Bringing as main theorists Augusto Boal (2013) and Viola Spolin (2001; 2010). Presenting as final result the report of the experience in the field and the didactic material produced in it.